The Relationship Between Expenditure and Regional Revenue of Palopo City in The Period 2019-2022 - Bakhtiar Bakhtiar; Budiarti Putri Uleng (IAIN Palopo, 2023)
This research aims to determine the types of revenue of Palopo City in supporting Palopo City Regional Expenditures. The variables studied consist of local original income, balancing funds, regional loans, other legal revenues, regional expenditure consisting of Operational Expenditures, Capital Expenditures and Unexpected Shopping and others. In this research, the Qualitative Descriptive Method was used.The results of the research show that regional revenues such as PAD, balancing funds and regional financial assistance have increased every year and the realization of regional expenditure has increased every year. Regional spending is greater than revenue, so there is a budget deficit.